Strategi Gerakan Sosial Komunitas 1000 Guru Gorontalo Berbasis Travelling and Teaching serta Pemeriksaan Kesehatan Gratis untuk Kesejahteraan Masyarakat Atinggola - Sufriyanto Ibrahim; Haris Munandar; Sulistia Harun (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to describe the implementation of social activities by the 1000 Teachers Gorontalo Community, focusing on the Traveling and Teaching (TNT) program and free health check-ups in Atinggola District, North Gorontalo Regency. This community collaborates with volunteers and medical personnel to provide enjoyable education for children in remote areas and raise health awareness through free check-ups. A descriptive qualitative approach was used to understand the implementation of the program and its impact on the community through observation, in-depth interviews, and surveys. The results show that the TNT program, which combines education and tourism, successfully strengthened the relationship between volunteers and the community. The health check-ups provided direct benefits to communities that have difficulty accessing health services. The evaluation of this program revealed challenges such as limited time and medical personnel, but it still had a positive impact on improving the quality of education and health in the local community